DETERMINANTS OF NET INTEREST MARGIN OF DEPOSITORY INSTITUTIONS IN NIGERIA: EVIDENCE FROM AUTO REGRESSIVE DISTRIBUTED LAG (ARDL) ESTIMATION MODEL (American Journal of Business Management, Economics and Banking, 2026)
This research sought to empirically identify the factors that determine the net interest margin of deposit money banks in Nigeria. Exploring theoretical and previous empirical research on the subject matter identify numerous factors both at firm, industry and economy-wide levels that influence the banks' net interest margin. In this research, we focused on the industry and economic factors. Relevant variables within this category include: Real Gross Domestic Product (RGDP); Liquidity Ratio (LQDR); Money Supply (MNSP); Exchange Rate (EXCR); Total Bank Deposits (TBDP); Loans and Advances (LOAN); and Total Bank Assets (BKAS). Data was collected from the CBN and the NBS. For the purpose of the research, the Auto-Regressive Distributed Lag (ARDL) estimation technique was deployed on time series data for the period 1986 to 2024. Findings of the research revealed that RGDP, EXCR, TBDP and LOAN had a positive and statistically significant relationship with net the NIMG of DMBs in Nigeria while LQDR, MNSP had statistically significant negative relationship with net interest margin. Finally, Total Bank Assets (BKAS) had a positive but non-significant relationship with net interest margin. The research concluded that a wide spectrum of economic factors affect the net interest margin of deposit money banks in Nigeria. This research thus recommends that banks can maximize interest income by focusing strategic attention on those factors that have the most significant effect on net interest margin.